Áp dụng quản trị tinh gọn cho các doanh nghiệp dịch vụ bán lẻ tại Việt Nam - Nguyen Dang , Minh; Nguyen Dang, Toan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Using survey and in-depth interview techniques for a number of retail businesses and supermarkets in Hanoi, this study analyzes the existing wastefulness and its causes, and proposes a lean management model for the retail businesses and/or services in Vietnam. The model emphasizes the commitment of the leadership through their training policy (e.g., mind training and lean management methods and instruments) as well as the recognition and reward policy available for employees. As beneficiaries of these policies, they will proactively participate in the governance process, implement their tasks in accordance with the lean management approach, improve work efficiency, cut wasteful spending, and constantly improve the operational efficiency of the organization. The research findings are worth referring to for other service businesses across the country.